A Technical Review of BMS Performance Standard for Electric Vehicle Applications in Indonesia - Wahyudi Sutopo; Budhy Rahmawatie; Fakhrina Fahma; Muhammad Nizam; Agus Purwanto; B.B Louhenapessy; Evizal Abdul Kadir (Universitas Ahmad Dahlan, 2018)
The development of Battery Management System (BMS) standards in Indonesia has been carried out causing the FACTS approach. That's approach makes it possible to accommodate all stakeholder requirements. However, the approach has not yet considered a technical review of the regulated standards. Based on this, this study undertook a comprehensive review of BMS performance parameters set out in the standard. In order that the regulated standards not only accommodate the needs of stakeholders but also consider BMS technical studies in order not to impede the future development of BMS.